Handling severe asthma exacerbations: Current guidelines and techniques: A review of research for pharmacists and emergency medical services - AL Khathami, Mohammed Mesfer Musaed; Alsaeed, Abdulaziz Abdullah; Alareefi, Hind Saad; Alharbi, Sanad Samah; Al Jasser, Saleh Abdullatif; Alanazi, Amani Ayyadhah; Alsulami, Abdulkarim Hamed; Daghas, Ibrahim Ahmad; Alghamdi, Najlaa Saeed; Alharbi, Fahad Eid (International journal of health sciences, 2019)
Background: Asthma affects approximately 300 million people globally, with a significant prevalence of uncontrolled cases contributing to rising hospitalizations and healthcare costs. In Saudi Arabia, 64% of asthma patients experience uncontrolled symptoms. Effective management of severe asthma exacerbations is critical, yet many patients remain inadequately controlled even in advanced care settings. Aim: This review aims to synthesize current guidelines and techniques for handling and management of severe asthma exacerbations, focusing on optimizing therapeutic strategies and improving patient outcomes via pharmacists and Emergency medical services. Methods: The review systematically examines existing guidelines, including the Saudi Initiative for Asthma (SINA) and other international protocols. It evaluates various treatments such as inhaled bronchodilators, systemic steroids, anticholinergic agents, and newer therapies like magnesium sulfate and heliox. The review also considers the effectiveness of different diagnostic and monitoring tools. Results: Effective management of severe asthma exacerbations involves a multi-faceted approach. Key strategies include the use of inhaled bronchodilators (MDIs preferred over nebulizers), systemic steroids for moderate to severe cases, and oxygen therapy to address hypoxemia. Anticholinergic agents and magnesium sulfate may be used for severe exacerbations, though their benefits vary.